Attachment and Penetration of Acyclovir‐resistant Herpes Simplex Virus are Inhibited by Melissa officinalis Extract. (12th May 2014) - Astani, Akram; Heidary Navid, Mojdeh; Schnitzler, Paul
<x xml:space="preserve">Abstract</x> Medicinal plants are increasingly of interest as novel source of drugs for antiherpetic agents, because herpes simplex virus (HSV) might develop resistance to commonly used antiviral drugs. An aqueous extract of Melissa officinalis and the phenolic compounds caffeic acid, p‐coumaric acid and rosmarinic acid were examined for their antiviral activity against herpes simplex virus type 1 (HSV‐1) acyclovir‐sensitive and clinical isolates of acyclovir‐resistant strains in vitro. When drugs were added during the intracellular replication of HSV‐1 infected cells, no antiviral effect was observed by plaque reduction assay. However, Melissa extract interacted directly with free viral particles of two acyclovir‐resistant HSV strains at low IC50 values of 0.13 and 0.23 µg/mL and high selectivity indices of 2692 and 1522, respectively. The Melissa extract and rosmarinic acid inhibited HSV‐1 attachment to host cells in a dose‐dependent manner for acyclovir‐sensitive and acyclovir‐resistant strains. These results indicate that mainly rosmarinic acid contributed to the antiviral activity of Melissa extract. Penetration of herpes viruses into cells was inhibited by Melissa extract at 80% and 96% for drug‐sensitive and drug‐resistant viruses, respectively. Melissa extract exhibits low toxicity and affects attachment and penetration of acyclovir‐sensitive and acyclovir‐resistant HSVs in vitro. Copyright © 2014 John Wiley & Sons, Ltd.